Using Indigenous Pedagogy and Philosophy to Enrich Outdoor Education Curriculum - Boyce, Shannon (2015)
Thesis (Master, Education) -- Queen's University, 2015-04-19 16:13:38.73 What purpose does outdoor education (OE) serve? What are the overall objectives of outdoor education programs, and are these objectives helping students connect with the environment around them? These are fundamental questions that need to be raised in order to provide outdoor education opportunities that are meaningful and enjoyable, and that encourage environmental sustainability among students. Currently, in Ontario, there is no official Ontario Ministry of Education curriculum document for OE. In order for schools to offer OE, they must draw expectations from the physical education curriculum at the desired grade level. Thus, since there is no specific OE curriculum, students may not be receiving the teachings of OE such as being made aware of and learning how to appreciate the local environment, which may in turn prevent understandings of environmental sustainability. This thesis uses policy analysis to examine two curriculum documents that address the following research questions: 1. Does the course PPL30 in the Health and Physical Education (OME, 2000a) curriculum policy document include Overall Expectations that encourage knowledge about the practice of environmental sustainability? 2. Does the Native Studies (OME, 2000b) curriculum policy document, specifically the course within this document titled “Aboriginal Beliefs, Values, and Aspirations in Contemporary Society, Grade 11, College Preparation,” include Overall Expectations that encourage knowledge about the practice of environmental sustainability? Furthermore, this thesis references two Ontario policy documents that provide additional information about incorporating environmental sustainability throughout the curriculum: Acting Today, Shaping Tomorrow: A Policy Framework for Environmental Education in Ontario Schools (2009) and Ontario First Nation, Metis, and Inuit Education Policy Framework (2007). M.Ed.